Innovation and firm performance: The moderating role of intellectual capital among Chinese companies - Ren, Chunya; Ting, Irene Wei Kiong; Kweh, Qian Long; Zhang, Cheng (Penerbit Universiti Sains Malaysia, 2023)
This study examines the impact of innovation on firm performance and how intellectual capital (IC) moderates the association between innovation and firm performance. We apply an innovation index that measures the frequency of innovative related words, which appear in firm financial reports to proxy for innovation. IC is estimated through the value-added IC (VAICTM) model. This study analyses Chinese firm-year observations of financial profitability (firm value) datasets, which total 19,152 (18,276) over the years from 2007 to 2019. Results indicate that the innovation index is positively related to financial profitability and firm market value. Moreover, the moderating outcomes suggest that IC boosts the positive relationship between innovation index and firm performance. Overall, this study highlights the importance of having innovation and IC together for gaining firm competitive advantages and progressing profitably. That is, firms should be innovative and must manage their IC well.